Evaluasi Layanan Paud Islam Terpadu Melalui Monitoring dan Supervisi - wiyani, novan ardy (IAIN Syekh Nurjati Cirebon, 2022)
This study is intended to describe the evaluation process of integrated Islamic PAUD services carried out at the integrated Islamic PAUD al-Ikhlas, Dukuhturi village, Bumiayu sub-district, Brebes district. This study uses a qualitative approach to the type of phenomenological research. Data were collected by interview, observation and documentation techniques. The data that has been collected is then analyzed using the data analysis technique of the Miles and Huberman model which consists of the stages of data reduction, data display and verification. The results of the study indicate that the evaluation activities in supervisory activities as one of the managerial activities are carried out through monitoring and supervision activities. Monitoring activities are carried out by the head of the integrated Islamic PAUD by observing the teacher's performance directly, either on a scheduled or incidental basis. The result is that the problems faced by teachers are known in their work and alternative solutions are obtained. Then supervision activities are carried out through academic supervision and clinical supervision. The result of the two forms of supervision activities is that the pedagogic and professional competence of teachers is increasing.